The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0102-86502011000800009
|View full text |Cite
|
Sign up to set email alerts
|

Fructose and NAFLD: metabolic implications and models of induction in rats

Abstract: PURPOSE:The increase in fructose consumption is paralleled by a higher incidence of obesity worldwide. This monosaccharide is linked to metabolic syndrome, being associated with hypertriglyceridemia, hypertension, insulin resistance and diabetes mellitus. It is metabolized principally in the liver, where it can be converted into fatty acids, which are stored in the form of triglycerides leading to NAFLD. Several models of NAFLD use diets high in simple carbohydrates. Thus, this study aimed to describe the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
0
21
0
1
Order By: Relevance
“…NAFLD is strongly associated with obesity and insulin resistance and is currently conceptualised as the hepatic manifestation of metabolic syndrome (MS) . Growing evidence suggests that the fast‐growing and alarming epidemic of NAFLD is closely intertwined with the Westernisation of dietary patterns with an increasing intake of simple sugars, especially fructose …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAFLD is strongly associated with obesity and insulin resistance and is currently conceptualised as the hepatic manifestation of metabolic syndrome (MS) . Growing evidence suggests that the fast‐growing and alarming epidemic of NAFLD is closely intertwined with the Westernisation of dietary patterns with an increasing intake of simple sugars, especially fructose …”
Section: Introductionmentioning
confidence: 99%
“…Starting from the 1960s, a number of animal and human studies have reported associations with excessive fructose consumption and adverse metabolic effects, which may have important hepatic consequences (including the development of NAFLD). The potential role of fructose in the pathogenesis of NAFLD has thus recently gained mounting attention and has been previously reviewed in detail . However, the extent to which fructose consumption is playing a role in liver damage and failure has not yet been investigated fully.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAFLD is a common liver disease usually occurring in patients that do not habitually consume alcohol and manifesting as an excessive accumulation of triglycerides in the liver, leading to fat build-up and an increase in total liver weight of over 5%. The prevalence of fatty liver in obese and diabetic patients can reach 70–90% [2]. Fatty liver occurs either as simple steatosis (hepatic steatosis) or in combination with non-alcoholic liver inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…A primeira opção leva cerca de 90 dias para induzir o diabete, com resultados variáveis. Já a aloxana e a estreptozocina levam 24h para a indução do diabete (Castro et al, 2011).…”
unclassified